Effects of pyruvate administration on mRNA expression of inflammatory cytokines in adipose tissue and whole‐body glucose metabolism in male mice - Ando, Taichi; Takeda, Reo; Kano, Ryotaro; Kusano, Tatsuya; Nonaka, Yudai; Kano, Yutaka; Hoshino, Daisuke (Physiological reports, 2025)
Pyruvate administration leads to the accumulation of intracellular lactate in adipocytes and affects inflammatory cytokine production and whole‐body glucose metabolism. Therefore, the purpose of this study was to determine whether pyruvate administration improves the dysfunction of glucose metabolism induced by high‐fat diet (HFD) intake. In an acute experiment, intraperitoneal injection of male mice with sodium pyruvate (1 g/kg body weight) increased pyruvate and lactate concentrations in blood and epididymal white adipose tissue (eWAT). In a chronic experiment, male mice were divided into three groups: normal diet, HFD with saline administration (HFD + SAL), and HFD with sodium pyruvate administration (HFD + PYR); the HFD + PYR group was injected with pyruvate five times a week for 8 weeks. Insulin concentrations in the basal state and during an oral glucose tolerance test were significantly lower in the HFD + PYR group than in the HFD + SAL group. The mRNA expression of inflammatory cytokines (tumor necrosis factor‐alpha and interleukin 6) and a M2 macrophage polarity marker in eWAT was significantly higher in the HFD + PYR group than in the other groups. These results suggest that chronic pyruvate administration partially improves whole‐body glucose metabolic dysfunction in HFD‐fed mice, accompanied by increased mRNA expression of inflammatory cytokines and a M2 macrophage marker in the eWAT.